2023
DOI: 10.3390/antiox12030558
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Application of Calcium Ameliorates Salinity Stress Tolerance of Tomato (Solanum lycopersicum L.) and Enhances Fruit Quality

Abstract: Tomato is affected by various biotic and abiotic stresses, especially salinity, which drastically hinders the growth and yield of tomato. Calcium (Ca) is a vital macronutrient which plays physiological and biochemical roles in plants. Hence, we studied the protective roles of Ca against salinity stress in tomato. There were eight treatments comprising control (nutrient solution), 5 mM Ca, 10 mM Ca, 15 mM Ca, 12 dS m−1 NaCl, 12 dS m−1 NaCl + 5 mM Ca, 12 dS m−1 NaCl + 10 mM Ca and 12 dS m−1 NaCl + 15 mM Ca, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 77 publications
(112 reference statements)
0
12
0
Order By: Relevance
“…Hydrogen peroxide (H 2 O 2 ) and malondialdehyde (MDA) content were determined as described previously by Islam et al [3].…”
Section: Hydrogen Peroxide and Melondealdehyde Determinationmentioning
confidence: 99%
See 3 more Smart Citations
“…Hydrogen peroxide (H 2 O 2 ) and malondialdehyde (MDA) content were determined as described previously by Islam et al [3].…”
Section: Hydrogen Peroxide and Melondealdehyde Determinationmentioning
confidence: 99%
“…After centrifuging the homogenates at 12,000× g for 30 min at 4 • C, the supernatant was collected and used to determine different enzyme activities. Catalase (CAT, EC: 1.11.1.6) activity was determined according to the method of Islam et al [3] through monitoring the decrease in absorbance at 240 nm for 1 min caused by the decomposition of H 2 O 2 with a spectrophotometer (Shimadzu, UV-1201; 1, Nishinokyo Kuwabara-cho, Nakagyo-ku, Kyoto 604-8511, Japan). Ascorbate peroxidase (APX, EC: 1.11.1.11) activity was determined in accordance with the procedure used by Islam et al [3].…”
Section: Estimation Of Antioxidant Enzymatic Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this essential macronutrient can modulate the activities of ACC synthase and ACC oxidase, leading to a reduction in endogenous ethylene production by the plant, thus slowing the process of senescence. A study by Islam, et al 21 showed an increase in antioxidant responses in tomato plants after the application of exogenous Ca. Due to these bene cial properties, the application of Ca salts, such as calcium chloride, calcium phosphate, calcium citrate, calcium oxide, and calcium lactate, has been reported to signi cantly prolong the vase life of cut owers in various species, including Heliconia spp 22 , Gerbera 23 , and Gladiolus 24 .…”
Section: Introductionmentioning
confidence: 98%